Distribuição espacial da oferta de saúde no Brasil no contexto do mix público-privado - Lucas Resende de Carvalho (2017)
The present work aims at analyzing the health services supply in Brazil according to a mixed health system. More specifically, the spatial distribution of total hospital beds, ICU beds, magnetic resonance (MRI) and mammography equipment is analyzed. Although the public and private health systems are intertwined in the provision, funding and demand for health services, their organization and operation logic differ. Whilst the private sector rationale is profit maximizing, the public sector aims at assuring the access to health services in an equitable fashion. The different rationales between both systems manifest in the spatial distribution of their provision. Taking the Central Place Theory developed by Christaller (1966) as reference, while the private sector supply is more ubiquitous across the territory, the public sector operates specifically in larger cities to benefit from economies of scale. Moreover, the level of complexity of a given service is crucial to determine its location in space. Mammography equipment, being less complex, less costly and of more intensive use, have a higher and more interiorized supply then MRI equipment. These, in turn, are located exclusively in cities with more than 20 thousands inhabitants. The hierarchy in the organization of the public health system through intermunicipal arrangements is an efficient mechanism in providing a minimum supply in most cases. Apart from MRI equipment, the existing supply in the country is enough to attend the minimum demand estimated by the Health Ministry. Nonetheless, regionally the distribution is not efficient to guarantee equitable access. Different clusters with deficit and surplus supply could be identified. It is common knowledge that inefficiencies arise from a mixed health system. Therefore it is crucial that quality information is available, especially concerning the private sector, to allow the implementation of more efficient regulations concerning the funding and the organizations of both systems, as well as delimiting more effectively what is public and what is private.